The factors that influence muslim investor to make gold investment / Nur Ameera Aireena Mustaffa - Mustaffa, Nur Ameera Aireena (Faculty of Business Management, 2018)
Gold is the most malleable, ductile, dense, conductive, non-destructive and beautiful metal. This had made it the most desired object for most of human history and in almost every civilization and there have been active gold market for over 6000 years (Green, 2007). Since the prehistoric time, people had used gold in trading and as a value keeping asset. Gold had been managed to maintain its value through the ages. The main reason is that unlike any other instruments such as paper currency, gold had been a stable way to pass on and preserve the value of wealth from one generation to the next. Besides, gold is one of the oldest precious metal that have been used for investment, currency, commodity and an object of beauty all around the world. By the time, gold had been widely recognised as the standard form of medium of exchange for international trade. Gold investment had been booming in recent years as many investors had become aware about the benefit of gold and its special features.The purpose of this research was to identify the factors that influence Muslim investors in Kedah to make gold investment. The factors of investors decision to make gold investment was also being study between risk of gold, hedge against inflation and safe haven. Respondents of this research was 100 which consists of Muslim investors who had made the gold investment. The questionnaires that was used to measure the investors decision to make the gold investment and the factors that influenced them to make the gold investment was designed from the previous researcher. The questionnaires was being used as it was easy for the researcher to collect and analysed the data obtained. The data were analyses using Statistical Package for Social Science (SPSS). Based on the multiple regression analysis, it was identified that the risk of gold factor is the main factor that influenced the Muslim investors to make the gold investment. Furthermore, safe haven and hedge against inflation had no relationship between them.